The Impact of Geo-Spatial Distribution of Markets on Household Travel Patterns in Akure Metropolis, Nigeria - Adetunji, Musilimu Adeyinka (Faculty of Economics and Business, Hasanuddin University, 2021)
This study examines the spatial distribution of markets and its impact on household travel patterns in Akure, Nigeria. Both primary and secondary data were utilized for the research. The coordinates of locations of markets were obtained using a hand held Geographical Position System (GPS) and determined by measured using the ‘Ruler’ menu of ArcGIS 10.3.1 software. A structured questionnaire was designed to elicit information on household travel patterns. Using descriptive and inferential statistics, the findings reveal that market is randomly distributed. A linear association exits between distance travel to market and household mode choice of transportation and it is significant at 0.05%. Inadequate transport services and traffic congestion are problems faced by households in Akure on their trips to markets. The study concludes that more periodic or daily markets should be provided in some localities that do not have in Akure and similar other cities in Nigeria.